Effect of the addition of CeO2 nanoparticles on the microstructure and shear properties of Sn–57Bi–1Ag solder alloy - Lei Zhang; Wenchao Yang; Junli Feng; Weiou Qin; Da Qi; Shijie Song; Yongzhong Zhan (Journal of Materials Research and Technology, 2023)
In this study, different weight fractions (0, 0.2, 0.5, 0.7, and 1.0 wt%) of cerium oxide (CeO2) nanoparticles were used to enhance the properties of Sn–58Bi–1Ag (SBA) solder alloys. As expected in the design, the CeO2 nanoparticles are diffusely distributed in the solder matrix. The microstructure evolution, growth of intermetallic compound (IMC) at the interface, and shear properties of the composite solder were systematically investigated using a scanning electron microscope (SEM) equipped with energy-dispersive X-ray spectroscopy (EDS) and electron backscatter diffraction (EBSD) probes. The results showed that adding an appropriate amount of CeO2 nanoparticles can refine the microstructure of the composite solder. Many β-Sn twin structures were observed in the SBA-0.5CeO2 and SBA-0.7CeO2 solder matrix, bringing better deformability to the β-Sn phase and improving the plasticity of the solder matrix. Moreover, with the addition of nanomaterials, there was a notable decrease in the thickness of the interfacial IMC layer of the solder/Cu joint, accompanied by a refinement in the grain size of the IMC. To our satisfaction, the addition of CeO2 nanoparticles in the appropriate proportion exhibited a remarkable enhancement in both shear strength and toughness of the composite solder alloys, working in tandem to transform the fracture mechanism from a purely brittle mode to a mixed mode of ductility and brittleness. It is indicated that the doping of CeO2 improves the reliability of SBA solder, potentially paving the way for a novel approach to particle-enhanced modification of Sn–Bi–Ag-based low-temperature solders.